Xanthogranulomatous Salpingitis Associated with a Large Uterine Leiomyoma - Joanne Margaret Howey; Etienne Mahe; Jasim Radhi (Case Reports in Medicine)
A case of xanthogranulomatous salpingitis (XGS) associated with a large uterine leiomyoma in a 50-year-old woman is presented. Xanthogranulomatous inflammation is an uncommon form of chronic inflammation that is destructive to affected organs. It is characterized by the presence of lipid-filled macrophages with admixed lymphocytes, plasma cells, and neutrophils. A review of the literature revealed that most patients with XGS have a clinical history of long-standing pelvic inflammatory disease (PID) or, less often, endometriosis. We report a case lacking a history of either PID or endometriosis but with a concurrent large uterine leiomyoma. Although the exact etiology in this case was not clear, the leiomyoma may have played a contributory role in pathogenesis.